2018
DOI: 10.12669/pjms.343.14922
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Decision Making Levels of Nursing Students

Abstract: Objective:The present study was conducted to determine nursing students’ levels of ethical decision-making.Methods:The sample of the descriptive study consisted of 240 nursing students. The data were collected using the Student Information Form and “Nursing Dilemma Test”.Results:It was found that Principled Thinking (PT) mean score (48.38±7.97) of nursing students was above average while their Practical Consideration (PC) mean score (17.87±4.13) was close to average. It was also determined that the nursing stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 12 publications
3
40
2
1
Order By: Relevance
“…Consistent with various related research results, our findings revealed that students adhere to ethical principles when making moral decisions. 33,44 The practical consideration scores in the NDT show that environmental factors—including number of patients, amount of resources, institutional policies, perceived administrative support, and physician control—are all taken into account when making decisions about ethical problems. 33 In this study, the decrease of practical consideration scores in the standardized patient group in our study suggests that students were unable to control factors arising from the standardized patient and/or the practice setting.…”
Section: Students’ Moral Sensitivitymentioning
confidence: 99%
“…Consistent with various related research results, our findings revealed that students adhere to ethical principles when making moral decisions. 33,44 The practical consideration scores in the NDT show that environmental factors—including number of patients, amount of resources, institutional policies, perceived administrative support, and physician control—are all taken into account when making decisions about ethical problems. 33 In this study, the decrease of practical consideration scores in the standardized patient group in our study suggests that students were unable to control factors arising from the standardized patient and/or the practice setting.…”
Section: Students’ Moral Sensitivitymentioning
confidence: 99%
“…Demirsoy et al () reported that nurses aged 26‐38 were deficient in their ability to evaluate ethical problems in line with ethical principles. In the study of Sari et al (), second‐year students had higher scores in the ethical decision‐making process than fourth‐year students. This situation was thought to since recently graduated and ethically trained students were more up‐to‐date.…”
Section: Discussionmentioning
confidence: 97%
“…The nurses with a Bachelor’s degree were more likely to detect ethical violations than those with other levels of education. It has been stated that when faced with ethical problems, nursing students studying at the undergraduate level were capable of making decisions by ethical principles (Sari et al ). It can be argued that this result was due to the ethics training received during their undergraduate nursing education.…”
Section: Discussionmentioning
confidence: 99%
“…And ethical character is a person's ability to overcome fatigue and di culties when implementing ethical actions [10]. Insu cient EDM competence can not only result in undesired outcomes, but also trap the decision-makers into ethical con icts [11].…”
Section: Introductionmentioning
confidence: 99%